MAKNA BERAGAMA MENURUT IMMANUEL KANT DALAM RELIGION WITHIN THE LIMITS OF REASONALONE - Imam Iqbal (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2015)
The searching oflmmanuel  Kant's thought in this paper will try to explain his ideas concerning to the meaning of religion from his critical philosophical perspective by set up from his work Religion within the Limits of Reason Alone. That work, will show later, is one of important Kant's work, especially concerning the relation between reason, religion, and morality. Although Religion could be classified as a work in philosophy of religion's field, however Kant's writing style in this work was not in popular fashion as commonly the work in philosophy of religion's field to be written. Kant's views ofreligion and the meaning ofbeing religious in this work are closely related to the moral frame work that he explained in his other works. The writer underlines some important points of Kant's thoughts: First, Religion has showed Kant's interest to religious problems, especially concerning religious meaning, in relation to morality and rationality. Second, the main discussion in Religion is about religious meaning. Third, Kant's explanation to religious meaning in Religion could be traced in to areas, i.e. individual area and social-community area. Fourth, the core of religious meaning in Religion is situated to Kant's implicit invitation to shift from just as ''having religion" to the ''being religious", or from having religious falsely to being religious authentically. Fifth, being religious or to be religious authentically is a representation of critical religious attitude.